2020
DOI: 10.1186/s12912-020-00507-w
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge, attitude, and fall prevention practices at south Korean hospitals: a cross-sectional survey

Abstract: Background Fall-prevention activities are nursing interventions which are designed to improve patient safety. The introduction of evaluations of medical institutions and an increase in medical litigation has led institutions to emphasize the importance of fall-prevention activities. The current situation regarding falls among patients in small and medium-sized hospitals is poorly understood. This study assessed knowledge and attitudes regarding falls, and fall-prevention activities of nurses working in small- … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Cho y col. (23) reportan que las actitudes sobre las caídas se relacionaron positivamente con la participación en actividades de prevención de caídas (r = 0,25, p = 0,001), pero no se observaron relaciones significativas entre el conocimiento de las caídas y la participación en actividades de prevención de caídas (r = -0,09, p = 0,267) o el conocimiento de las caídas y las actitudes hacia ellas (r = 0,09, p = 0,240).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Cho y col. (23) reportan que las actitudes sobre las caídas se relacionaron positivamente con la participación en actividades de prevención de caídas (r = 0,25, p = 0,001), pero no se observaron relaciones significativas entre el conocimiento de las caídas y la participación en actividades de prevención de caídas (r = -0,09, p = 0,267) o el conocimiento de las caídas y las actitudes hacia ellas (r = 0,09, p = 0,240).…”
Section: Discussionunclassified
“…Los hallazgos descritos anteriormente indican que debe implementarse una educación consistente y recurrente para la prevención de caídas adaptada a los hospitales pequeños y medianos para promover el compromiso con las actividades de prevención de caídas. (23) La promoción de cambios en las actitudes con respecto a las caídas mediante la introducción de programas de refuerzo de actitudes que tengan en cuenta las normas subjetivas de las enfermeras debe mejorar su sentido de la responsabilidad y actuar cotidiano. (32)…”
Section: Discussionunclassified
“…In this study, 56% of the control group just had a primary school education or below, and it was 62% in the observation group, which was similar to the results of Cho MY. [ 14 ] On the other hand, it may be that the caregivers had not received professional trainings about how to prevent fall. Gu YY [ 15 ] pointed out that the main way for caregivers to acquire fall-related knowledge is through personal life experience and hospital training.…”
Section: Discussionmentioning
confidence: 99%
“…is fed back on a continuing basis to help maintain engagement. A study of 162 nurses from South Korean hospitals found a positive correlation between nurses' attitudes regarding patient falls and the execution of fall prevention activities [25]. As suggested by the ERIC tool [2], there is a need for consistent, repeated and customised fall prevention education to promote engagement in fall prevention activities.…”
Section: Enablersmentioning
confidence: 99%